Multiplicity of solutions for asymptotically linear $n$-th order boundary value problems - Dalbono, Francesca (Topological Methods in Nonlinear Analysis, 2007)
In this paper we investigate existence and multiplicity of solutions, with prescribed nodal properties, to a two-point boundary value problem of asymptotically linear $n$-th order equations. The proof follows a shooting approach and it is based on the weighted eigenvalue theory for linear $n$-th order boundary value problems.